2022
DOI: 10.1111/1475-679x.12424
|View full text |Cite
|
Sign up to set email alerts
|

Real Effects of a Widespread CSR Reporting Mandate: Evidence from the European Union's CSR Directive

Abstract: We investigate real effects of a widespread corporate social responsibility (CSR) reporting mandate. In 2014, the European Union (EU) passed Directive 2014/95 (hereafter, "CSR Directive"), mandating large listed EU firms to prepare annual nonfinancial reports beginning from fiscal year 2017 onward. We document that firms within the scope of the directive respond by increasing their CSR activities and that they start doing so before the entry-into-force of the directive. These real effects are concentrated in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(45 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…A higher value of discretionary accruals indicates greater amounts of accrual-based earnings management (AEM) and thus greater information asymmetry. 4 We follow Fiechter, Hitz and Lehmann (2022) and use CSR controversies as a measure of the information asymmetry-related CSR practices of the firm. Using ESG controversies as a measure of information asymmetry yielded consistent results.…”
Section: Additional Analysismentioning
confidence: 99%
“…A higher value of discretionary accruals indicates greater amounts of accrual-based earnings management (AEM) and thus greater information asymmetry. 4 We follow Fiechter, Hitz and Lehmann (2022) and use CSR controversies as a measure of the information asymmetry-related CSR practices of the firm. Using ESG controversies as a measure of information asymmetry yielded consistent results.…”
Section: Additional Analysismentioning
confidence: 99%
“…France or Denmark, large companies have been required to produce CSR reports for a long time. The EU Directive 2014/95, which mandates CSR reporting by large listed companies in the EU, has been demonstrated to have effects on the CSR activities of the affected companies (Fiechter et al, 2022). In a similar vein, it has been found that companies -contingent upon a series of pressures -pay interest to what their own country perceives as important (Amor-Esteban et al, 2018).…”
Section: Headquartersmentioning
confidence: 97%
“…Program's effects more completely, I explore emission responses prior to disclosure. Facilities knew as early as April 2009 that their emissions would be publicly disclosed, and thus they might have anticipated stakeholder pressure (e.g., Fiechter, Hitz, and Lehmann [2022]). The U.S.…”
Section: Ghg Emission Responses Prior To Us Program Disclosurementioning
confidence: 99%